Animal Female Meiosis: The Challenges of Eliminating Centrosomes - Oliver J. Gruss (Cells, 2018)
Sexual reproduction requires the generation of gametes, which are highly specialised for fertilisation. Female reproductive cells, oocytes, grow up to large sizes when they accumulate energy stocks and store proteins as well as mRNAs to enable rapid cell divisions after fertilisation. At the same time, metazoan oocytes eliminate their centrosomes, i.e., major microtubule-organizing centres (MTOCs), during or right after the long growth phases. Centrosome elimination poses two key questions: first, how can the centrosome be re-established after fertilisation? In general, metazoan oocytes exploit sperm components, i.e., the basal body of the sperm flagellum, as a platform to reinitiate centrosome production. Second, how do most metazoan oocytes manage to build up meiotic spindles without centrosomes? Oocytes have evolved mechanisms to assemble bipolar spindles solely around their chromosomes without the guidance of pre-formed MTOCs. Female animal meiosis involves microtubule nucleation and organisation into bipolar microtubule arrays in regulated self-assembly under the control of the Ran system and nuclear transport receptors. This review summarises our current understanding of the molecular mechanism underlying self-assembly of meiotic spindles, its spatio-temporal regulation, and the key players governing this process in animal oocytes.